Literary Planning and Development in Indonesia Through The Local Literature Community (LLC): A Challenge - Sulaiman Sulaiman; Mintowati Mintowati; Anas Ahmadi (Journal of Development Research, 2020)
Planning and fostering literature in Indonesia is very important as an effort to preserve it, especially regional literature and develop its existence. This is important because literature has a noble function, namely voicing the heart and phenomena that occur in society. We see that the development of literature in Indonesia such as "living reluctantly to death does not want", is in a situation and condition of concern. Attention from the government and the community is still very minimal. Even though literature in Indonesia still seems to exist, it is solely due to literary activists, both individuals and communities who still care and love literature. This presents a challenge. Challenges in planning and developing literature in Indonesia. It is time for literary issues in Indonesia to be seriously designed by involving people or people who have concerns. Does not always depend on the country. Therefore, independence is needed in discussing the planning and development of literature in Indonesia. In this case the direct involvement of activists / local literary communities is needed. This thinking originated from several existing communities and can survive and even flourish in producing writers and developing literary works in Indonesia. Thus, it is not impossible if the Local Literature Community will provide encouraging results on the development of literature in Indonesia.